Reduction of matrix metalloproteinase 8-neutrophil collagenase levels during long-term doxycycline treatment of reactive arthritis. - Lauhio, A (1994)
The aim of this work was to determine whether human polymorphonuclear neutrophilic interstitial collagenase (matrix metalloproteinase 8 [MMP-8]) levels are reduced during long-term doxycycline treatment in humans with reactive arthritis. Serum MMP-8 levels were reduced (mean +/- standard error of the mean, 678.9 +/- 185.6 versus 491.2 +/- 144.8 ng of MMP-8 per ml), but not statistically significantly. However, the reduction of salivary MMP-8 levels was statistically significant (3,729 +/- 1,905.3 versus 1,866 +/- 780.0 ng of MMP-8 per ml, P < 0.05). This study demonstrated that a 2-month regimen of doxycycline can reduce MMP-8 levels in serum and especially in body fluids (i.e., saliva) containing inflammatory exudates and thus may contribute to reduced tissue destruction.